An Economic Evaluation on Scaling-up Production of Nano Gold from Laboratory to Industrial Scale - G. Miftahurrahman; H. Setiarahayu; A. B.D. Nandiyanto (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2019)
Gold nanoparticles are applicable in various engineering fields such as in biosensors, drug delivery, and tumor imaging. The objective of this study was to evaluate the scaling-up production of gold nanoparticles from laboratory to industrial scale. The evaluation was done from engineering and economic perspectives, in which several parameters including gross profit margin (GPM), and payback period (PBP) were analyzed. From the engineering evaluation, the result showed that the production of Nano gold is prospective using current technologies. To produce Nano gold, we could use chloroauric acid, sodium citrate, and sodium borohydride, in which these materials can be converted into gold nanoparticles. From the economic evaluation, the result showed that Nano gold production in industry scale can be profitable with a certain condition of raw material. It was shown that the breakeven point, payback period and gross profit margin could be achieved in 20 years.